Progress and opportunities in Gellan gum-based materials: A review of preparation, characterization and emerging applications. (1st July 2023) - Gomes, D.; Batista-Silva, J.P.; Sousa, A.; Passarinha, L.A.
Abstract: Gellan gum, a microbial exopolysaccharide, is biodegradable and has potential to fill several key roles in many fields from food to pharmacy, biomedicine and tissue engineering. In order to improve the physicochemical and biological properties of gellan gum, some researchers take advantage of numerous hydroxyl groups and the free carboxyl present in each repeating unit. As a result, design and development of gellan-based materials have advanced significantly. The goal of this review is to provide a summary of the most recent, high-quality research trends that have used gellan gum as a polymeric component in the design of numerous cutting-edge materials with applications in various fields.